Advanced Nanotheranostics of CRISPR/Cas for Viral Hepatitis and Hepatocellular Carcinoma (Adv. Sci. 24/2021). Issue 24 (22nd December 2021) - Kong, Huimin; Ju, Enguo; Yi, Ke; Xu, Weiguo; Lao, Yeh‐Hsing; Cheng, Du; Zhang, Qi; Tao, Yu; Li, Mingqiang; Ding, Jianxun
Abstract : CRISPR Nanotheranostics In article number 2102051, Yeh‐Hsing Lao, Qi Zhang, Yu Tao, Mingqiang Li, and co‐workers overview the recent advances of CRISPR nanotheranostics in tacking viral hepatitis and hepatocellular carcinoma. The nanoscale CRISPR/Cas systems could act as smart enzymatic robots to target the disease‐associated cells and nucleic acid signatures and may be potentially added to the armamentarium for efficiently addressing these challenging liver diseases.